Peningkatan Pemahaman Matematis Siswa SMAK Warta Bakti Kefamenanu Melalui Pembelajaran Berbantu Sudoku - Cecilia Novianti Salsinha; Eva Binsasi; Elinora Naikteas Bano (Universitas PGRI Adi Buana Surabaya, 2020)
Mathematics is one of the most important sciences in life, this can be seen from mathematics lessons that have even been learned since elementary school and even kindergarten. But learning mathematics is not always easy. Based on observations in the field, there are still many teachers in schools providing a less innovative learning, learning strategies that are still monotonous and learning methods that are less interesting.Based on data from the UN results in 2019 obtained from the Ministry of Education and Culture shows that NTT is one of 12 provinces where the average UN score is below the national average. Because mathematics is one of the UNBK subjects but occupies the lowest place of other subjects, the authors consider mathematics to be the center of attention, especially in the NTT region especially Kefamenanu. Therefore, the writer applies the sudoku game-assisted learning method to improve the understanding of the students of Warta Bakti Kefamenanu. The researcher compared the pre-test and post-test scores which gave the result that the scores were lower than the post-test scores. This confirms that students' understanding after learning by using the Sudoku game gives significant results.